THE REPRESENTATION OF FUNCTIONS BY WALSH DOUBLE SYSTEM IN WEIGHTED L_μ^p [0,1)^2 -SPACES - Simonyan, L.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2019)
In this work we construct a weighted space L_μ^p, p ≥ 1 , in which functions with the norm of that space are presented by Walsh double series, which coefficients are monotone in all ways.